The Influence of the Movie Zootopia on Improving 8th Grade Junior High School Students' Vocabulary Mastery - Ishmatul Muflihah; Nur Fauzia (Journal of English Language and Education, 2026)
Vocabulary mastery plays a crucial role in English language learning as it supports the development of speaking, listening, reading, and writing skills. However, the lack of engaging learning materials means that many junior high school students still struggle with vocabulary acquisition. This study aims to determine the effect of using the movie *Zootopia* on students’ vocabulary mastery. This study employed a pre-experimental design using a one-group pre-test and post-test model involving 31 eighth-grade students. Data were collected through a vocabulary test and analyzed using descriptive statistics and the Wilcoxon Signed-Rank test. The results showed that the mean score increased from 79.42 on the pre-test to 89.06 on the post-test, representing a 12.13% increase. Furthermore, the analysis revealed a significant difference (p 0.05). Thus, the use of the film Zootopia has a significant effect on improving students’ vocabulary mastery.